Penanaman Pendidikan Karakter sebagai Upaya Mencegah dan Mengurangi Kasus Bullying - Nadila Ardhia Garini; Bengkel Ginting; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Bullying cases nowadays are increasingly occurring in all circles. Bullies feel that what they do is normal. Even though bullying can have a very bad impact on the victim of bullying. The factors that cause bullying also vary. However, it is often found that the main cause is when a person's shortcomings are considered to be ridiculed by bullies, then they bully that individual without thinking about the impact on the victim. In this case, problems were found in groups of children where bullying often occurred among them when playing or studying. The author here carries out social work practice on PKL II assignments using the Groupwork Method with stages such as: (1) Engagement, Intake and Contract, (2) ssessmenAt, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. The aim of this practicum is to reduce cases of bullying using character education as part of the process of controlling emotions and developing self-control. The results of the implementation of this program show that cases of bullying in this group of children are decreasing.